Analyses of dermoscopic and reflectance confocal microscopic features of Paget disease - Xiu WANG; Lang RAO; Junru YE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To investigate polarized light dermoscopic and reflectance confocal microscopic features of Paget disease. Methods Dermoscopic and reflectance confocal microscopic features of 76 lesions were analyzed in 29 patients with Paget disease, who visited our clinic from January 2019 to October 2021. Results Among the 29 patients, including 18 males and 16 females, 9 cases were mammary Paget disease and 20 cases were extramammary Paget disease, with a total of 76 lesions. Polarized light dermoscopy showed milky-white structureless areas, bright white streaks, vascular structures and light brown to bluish gray dots in milky-red and reddish-brown background. Reflectance confocal microscopy examination of the lesions showed disorganized epidermal cells with vacuole-like cells and Paget cells, formation of tumor nests by Paget cells in the basal layer, tortuous blood vessels in the superficial dermis with infiltrate of inflammatory cells, dendritic cells and pigmentophages. Dermoscopic and reflectance confocal microscopic features were similar in Paget and extramammary Paget diseases. Conclusion Paget disease displays specific characteristics under the polarized light dermoscope and reflectance confocal microscope, providing a basis for non-invasive diagnosis of the disease.